Utilization of donor CLL-1 CAR-T cells for the treatment of relapsed of acute myeloid leukemia following allogeneic hematopoietic stem cell transplantation - Zhang, Meng; Zhang, Xiaomei; Wang, Jiaxi; Lu, Wenyi; Xiao, Xia; Lyu, Hairong; He, Xiaoyuan; Pu, Yedi; Meng, Juanxia; Lyu, Cuicui; Cao, Xinping; Zhao, Mingfeng (Frontiers in Immunology, 2025)
BackgroundHuman C-type lectin-like molecule 1 (CLL-1) represents a promising therapeutic target for Chimeric antigen receptor T (CAR-T) cells therapy in the treatment of acute myeloid leukemia (AML). In this study, we aimed to evaluate the efficacy and safety profile of donor-derived CLL-1 CAR-T cells in AML patients who experienced relapsed post-transplantation.Methods14 AML patients who experienced relapse following allogeneic HSCT were enrolled in our clinical trial. However, 2 patients withdrew from the study due to rapid disease progression. 12 participants received donor-derived CLL-1 CAR-T cells and were categorized into 3 groups based on the dosage of infused CAR-T cells dose (Group A:0.5×106/kg, Group B:1×106/kg, Group C:1.5×106/kg). And scRNA-seq was used to reveal CLL-1 CAR-T cells dynamics in a CAR-T cells infusion products and PBMCs at the peak of expansion for patient 4.ResultsCLL-1 CAR-T cells were well tolerated by all 12 patients. Cytokine Release Syndrome (CRS) was observed in all patients, with 5 patients experiencing grade ≥3. 3 patients developed cytokine release syndrome-associated encephalopathy (CRES), and 1 patient had a grade 4 severity level. All patients demonstrated a reduction in tumor burden, while 7 patients (58.33%) achieved MRD-CR and 2 patients (16.67%) reached MRD+CR. CAR-T cells expansion was detectable in all 12 patients, with the median time of peak expansion was 9 days (range: 7-11 days). In patient 4, compared to the pre-reinfusion state, CD4+ cells at the peak of expansion showed upregulation of cell killing-related genes and memory T cell-related genes (P < 0.01).ConclusionsThe CLL-1 CAR-T cells therapy derived from allogeneic donors demonstrates both safety and efficacy in the management of relapsed AML following allogeneic HSCT. And adjusting the ratio of CD4+ CAR-T cells and CD8+ CAR-T cells prior to infusion may help mitigate CAR-T cell-related side effects.Clinical trial registrationhttps://www.chictr.org.cn/, identifier ChiCTR2000041054.